Sustainable recreation planning with spatial analysis for trail and campsite characterization in Cameron Highlands, Malaysia - Mohd Sapian, Muhammad Shafeeq (2022)
Outdoor activities and the provision of recreational trails provide numerous benefits to health, human well-being, and education through nature appreciation and understanding. They can also increase environmental awareness, local economic development, connect major areas, and diversify the tourism market. However, trail development and design must adhere to the principles of sustainable recreation while understanding the perceptions of trail users. In the case of Cameron Highland, the forested area is facing a challenge to assess the resource condition as the complex mountain ecosystem limits researchers accessibility for ground monitoring. This study aims to demonstrate the use of geospatial technology methods using terrain analysis to assess and map the trail and campsite characteristics in the complex mountainous area of Cameron Highlands. Spatial assessment was carried out on Mount Irau which is located in the Batu Gangan Forest Reserve. The method used in this study comprises digital terrain assessment, field monitoring and verification. Terrain characteristics such as Slope, Topographic Wetness Index (TWI), Slope Length Factor (LS), and landform classification (LC) are automatically obtained by using a Digital Terrain Model with a resolution of 10 meters through the SAGA GIS platform. This study suggested that the hiking trail of Mount Irau is dominated by ridge landform type with a mean elevation value of 1572.46±171.48. The study found out that the trail slope of Mount Irau is erosive with a mean value of 19.16±9.53°, thus an alternative route has been proposed. Interestingly, the plain landform covers only 3.26% or 2.03km2 of the entire study area, where two potential camping sites have been identified. Results obtained from the study which were presented in the Geographical Information System (GIS) theme can be used for long-term project planning and produce effective management of recreational resources in the area.